Asymmetric Effects of Sustainability Indices in Emerging Asian Countries - Passah, Heibha; Ninan, Gregory George; Anuradha, P. S. (Indian Journal of Research in Capital Markets, 2020)
Sustainable investing has become quite popular in emerging Asian countries as many developing economies are adopting it in their financial markets. This study aimed to analyze the asymmetric effect on the volatility of sustainability indices of five Asian emerging countries, that is, Korea, India, China, Indonesia and Malaysia, along with a developed nation’s sustainability index, that is, USA using the exponential GARCH model. The paper also examined the movement of indices alongside each other using the correlation coefficient. The results indicated that even though the indices were correlated, there was an asymmetric impact on the volatility of the indices of emerging Asian countries. This will enable Asian investors to make better decisions regarding their portfolio diversification and selection.